Padronização de testes neurocomportamentais para investigação da importância funcional do wulst visual em corujas buraqueiras (Athene cunicularia) - Leticia Mercedes Gomes Correia Martins (2012)
Birds have been used in numerous researches involving visual-cognitive skills and is an excellent model for comparative neurobiology. Several researches have shown in most birds, especially those with lateral eyes, that the main visual pathway is retinotetofugal unlike mammals whose main visual pathway is retinotalamofugal. Owls, however, have as main pathway retinotalamofugal wich neuronal projections terminate in a telencephalic region called wulst and particularly developed in these birds. There are many datas on the morphological and physiological organization of visual wulst owls, although the functional role of this structure has not yet been proven. This project aims to establish a battery of suitable tests for assessing the behavioral consequences of a lesion in the visual wulst burrowing owl (Athene cunicularia) and the functional role of this region using aneurobehavioral approach. Among the tests performed, the balance of animals was assessed through an apparatus especially developed for this test. Beyond that, the preference light-dark was evaluated by adjusting the test light / dark used with rats and mice. The behavioral repertoire was analyzed by an ethogram where they were highlighted visual-motor behaviors. There was no statistically significant difference(p> 0.05) for these tests before and after the injury wulst. The pupillometry showed differences in pupillary reflex before and after the lesion of 2 owls. It was observed that after injury pupillary responses were statistically slower. Te visual discrimination task revealed the threshold of an owl in the discrimination of stimulus consisting of sinusoidal gratings arranged horizontally (threshold of 0.96 °) and vertically (threshold of 2.03 °). An owl subjected to discrimination visual with stimulus test of faces and no faces showed a good performance in this task, however, did notrespond to the test after the injury